2006
DOI: 10.1093/schbul/sbl047
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Anomalies in Schizophrenia: Integrating Phenomenology and Cognitive Neuroscience

Abstract: From phenomenological and experimental perspectives, research in schizophrenia has emphasized deficits in "higher" cognitive functions, including attention, executive function, as well as memory. In contrast, general consensus has viewed dysfunctions in basic perceptual processes to be relatively unimportant in the explanation of more complex aspects of the disorder, including changes in self-experience and the development of symptoms such as delusions. We present evidence from phenomenology and cognitive neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(174 citation statements)
references
References 61 publications
13
155
0
6
Order By: Relevance
“…This is consistent with a more general deficit people with schizophrenia show in terms of processing faces and whole-body emotional expressions (Chan et al 2010;Van den Stock et al 2011). These disturbances reflect well-documented difficulties with "perceptual organization" in schizophrenia, including a fragmentation of space and object perception (Silverstein et al 2017;Uhlhaas and Mishara 2007). These disruption manifests via various phenomenological anomalies: e.g., figure-ground confusion, "visual echoes", loss of perceptual stability, etc.…”
Section: Disturbances Of Embodied and Social Scaffoldingsupporting
confidence: 73%
“…This is consistent with a more general deficit people with schizophrenia show in terms of processing faces and whole-body emotional expressions (Chan et al 2010;Van den Stock et al 2011). These disturbances reflect well-documented difficulties with "perceptual organization" in schizophrenia, including a fragmentation of space and object perception (Silverstein et al 2017;Uhlhaas and Mishara 2007). These disruption manifests via various phenomenological anomalies: e.g., figure-ground confusion, "visual echoes", loss of perceptual stability, etc.…”
Section: Disturbances Of Embodied and Social Scaffoldingsupporting
confidence: 73%
“…Together with the role of TC-interactions for the selection of relevant sensory inputs, these data highlight the possibility that dysfunctional TC-interactions may contribute towards the characteristic changes in self-experiences at the onset of psychosis, such as the reduced ability to differentiate between relevant and irrelevant information, a symptom commonly observed in the early stages of ScZ (McGhie and Chapman, 1961;Uhlhaas and Mishara, 2007). Moreover, an additional manifestation of aberrant TC-interactions are the changes in sleep-patterns that predate the onset of psychosis (Zanini et al, 2015) as well as the reductions in sleep-spindels observed in EEG-recordings in FEP-patients (Manoach et al, 2014) (see also Ferrarelli and Tononi in this issue).…”
Section: (2012) For a Different Finding)mentioning
confidence: 80%
“…This is supported through data from anatomy (Selemon et al, 1995), physiology (Rivolta et al, 2014;Sun et al, 2013;Grützner et al, 2013;Krishnan et al, 2005;Butler et al, 2007) and psychophysics (Butler et al, 2008;Uhlhaas and Silverstein, 2005;Uhlhaas and Mishara, 2007), which has highlighted that the earliest stages of auditory and visual processing might be compromised. As a result, dysfunctions in "higher" cortical regions that support more complex cognitive processes involved in executive functions and social cognition could be essentially due to deficits in bottom-up driven sensory activity (Javitt, 2009).…”
Section: Introductionmentioning
confidence: 93%